Mouse in space! - STILTON, GERONIMO; GERONIMO STILTON (New York Scholastic Inc, 2013)
a high-flying adventure where Geronimo is recruited for a top-secret mission to save New Mouse City from an evil professor.
Keywords: It follows the reluctant journalist-mouse on a top-secret mission to outer space; the value of bravery, and the importance of teamwork and friendship